The association between anosognosia and neuropsychiatric symptoms in neurodegenerative dementias: a narrative review - Gallingani, Chiara; Tondelli, Manuela; Vannini, Patrizia; Zamboni, Giovanna (Frontiers in Neurology, 2025)
Anosognosia, or unawareness of disease, is a common clinical feature in neurodegenerative dementias. Frequently reported as an early symptom, its presence has been associated with faster dementia progression and greater cognitive impairment. Similarly, neuropsychiatric symptoms (NPS) encompass non-cognitive behavioral and psychiatric disturbances that commonly affect individuals with dementia. Both aosognosia and NPS are clinically relevant in neurodegenerative diseases due to their significant implications in disease management and caregiver burden. In this narrative review, we examined studies investigating the direct relationship between anosognosia and NPS across different neurodegenerative dementias, including Alzheimer’s Disease (AD), Frontotemporal Dementia (FTD) and α-synucleinopathies, such as Parkinson’s Disease (PD) and Dementia with Lewy Bodies (DLB). A total of 46 studies were identified, the majority of which focused on AD. Despite considerable heterogeneity in participant selection, assessed domains, and measures of anosognosia and NPS investigated, consistent association emerged between anosognosia and global NPS scores as well as individual symptoms. Across studies, the most common finding was a negative association between anosognosia and depression and a positive association between anosognosia and apathy. Possible underlying mechanisms and shared neuroanatomical substrates of these findings are discussed. The review provides a deepened insight into key symptoms with critical implications for dementia research, clinical management, and caregiving strategies.